1988
DOI: 10.1002/ange.19881000107
|View full text |Cite
|
Sign up to set email alerts
|

Natürliche Fette und Öle – nachwachsende Rohstoffe für die chemische Industrie

Abstract: Natiirliche Fette und Olenachwachsende Rohstoffe fur die chemische Industrie Angcw. Chem. 100 (1988) 41-62 0 VCH Verlagsgesellschaft mbH. D-6940 Weinheim. 1988 Das Vorsatzblatt zeigt als Beispiel fur nachwachscnde Rohstoffe (im Ilhneigersinn. oben Mitte beginnend): Sojabohnen, Rapssamen, Rhizinusbohnen. Olleinsamen, Jojobasamen und Sonnenblumenkerne: in der Mitte des Bildes sind Teile einer Kokospalme mit Friichten zu sehen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0
12

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(70 citation statements)
references
References 153 publications
0
58
0
12
Order By: Relevance
“…Evaporation of the pentane followed by kugelrohr distillation gave 5 carbon compounds is based on the tetrahedron model of methane. [2] Nowadays this geometry is well known in molecular science. Moreover, isoelectronic molecules and ions usually adopt classical tetrahedral structures too.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Evaporation of the pentane followed by kugelrohr distillation gave 5 carbon compounds is based on the tetrahedron model of methane. [2] Nowadays this geometry is well known in molecular science. Moreover, isoelectronic molecules and ions usually adopt classical tetrahedral structures too.…”
Section: Methodsmentioning
confidence: 98%
“…[10] The analogous PR 4 ion has not yet been prepared, but ab initio calculations predict the same tetragonal pyramidal geometry as observed for AsR 4 . [11] In our search for a stable tetrametalated phosphonium salt (PR 4 X À , R metal ligand, X any counterion), we found that the tetrametalation of the triphosphenium salt 1 [12] with the Schwartz reagent [(C 5 H 5 ) 2 ZrHCl] (2) [13,14] in the molar ratio of 1:9 in THF and in the presence of triethylamine as an auxiliary base surprisingly leads to the tetrazirconio-substituted phosphonium cation in 3, which adopts an ªanti-vant Hoff ± Le Belº configuration. Compound 3 is diamagnetic, sparingly soluble in aromatic solvents, THF, and CH 2 Cl 2 , but soluble in DMF (but slow decomposition occurs), and has been isolated in an analytically pure state (correct C,H combustion analysis) in the form of green crystals in 11 % yield.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation of the world polity and regional wars are not left out, because their underlying reasons and interest are centered on this limited and non-ecofriendly based material (petroleum) [1][2][3] . Sustainable resource materials like cellulose and starch, proteins, natural rubber and vegetable seed oils are capable of providing eco-friendly chemicals and polymeric based feeds as substitute to petroleum feed stocks 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In the field of oleochemistry the ene reaction has received only little attention over the past decades, although the reaction products -highly functionalised oleochemicals with a branched alkyl chain -could be very interesting for many industrial applications [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%